Clinical Profile of COVID-19 in Indigenous People in Manaus-AM (Research, Society and Development, 2022)
Objective: Describe the clinical profile of covid-19 in indigenous people in Manaus-AM, in the health of indigenous peoples, identify and understand how the virus develops. Methodology: present the way that COVID behaves in the indigenous organism; taking into account their vulnerabilities to epidemics in terms of social, economic and health conditions worse than non-indigenous people, which amplifies the potential spread of diseases. Results: the nutritional status and emerging chronic diseases. Emphasis is given to poor sanitation conditions verified in the villages, the high prevalence of chronic malnutrition, anemia, diarrhea and acute respiratory infections in children, and the emergence of chronic non-communicable diseases in women. Conclusion: The scenario outlined from the Survey requires an urgent critical review of indigenous health policy, with a view to better meeting the health needs of the indigenous segment of the Brazilian population.